2022
DOI: 10.3389/fnut.2022.969887
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between circulating selenium level and the risk of schizophrenia in the European population: A two-sample Mendelian randomization study

Abstract: BackgroundThe association between circulating the selenium level and the risk of schizophrenia remains unclear.ObjectiveTo determine the relationship between the circulating selenium level and the risk of schizophrenia, using the Mendelian Randomization method in the European population.MethodsSingle nucleotide polymorphisms (SNPs) associated with the circulating selenium level were identified at p < 5 × 10−8. The inverse variance weighted (IVW) method was used as the principal MR analysis, and MR Egger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The LDSC method indicated that genetic variants related to depression [ r g = 0.157, se = 0.023, p = 3.52×10 -12 ] and SCZ ( r g = 0.042, se = 0.020, p = 0.042) were positively correlated with AAA, while BIP was not ( r g = 0.013, se = 0.023, p = 0.591). Additionally, the GNOVA method estimates further supported these findings, indicating a positive association of AAA with depression ( r g = 0.152, se = 0.019, p = 8.41× -16 ) and SCZ ( r g = 0.053, se = 0.017, p = 0.002). Conversely, BIP did not demonstrate a significant association with AAA ( r g = 0.021, se = 0.019, p = 0.272).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The LDSC method indicated that genetic variants related to depression [ r g = 0.157, se = 0.023, p = 3.52×10 -12 ] and SCZ ( r g = 0.042, se = 0.020, p = 0.042) were positively correlated with AAA, while BIP was not ( r g = 0.013, se = 0.023, p = 0.591). Additionally, the GNOVA method estimates further supported these findings, indicating a positive association of AAA with depression ( r g = 0.152, se = 0.019, p = 8.41× -16 ) and SCZ ( r g = 0.053, se = 0.017, p = 0.002). Conversely, BIP did not demonstrate a significant association with AAA ( r g = 0.021, se = 0.019, p = 0.272).…”
Section: Resultsmentioning
confidence: 59%
“…These findings enhance the statistical power and offer the opportunity to explore their genetic associations. In addition, Mendelian Randomization (MR), which uses genetic variants (single nucleotide polymorphisms, SNPs) as instruments, is a powerful method for obtaining robust causal inference 15 and has been widely utilized in recent epidemiological research 1618 . As a result, this study aims to investigate the genetic correlation between AAA and mental disorders and to utilize the MR design to evaluate their causality.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic epidemiology established another approach to address these conundrums. Mendelian randomization (MR) is a genetic instrumental variable analysis approach based on genetic variants associated with the exposures of interest, which serve as un‐confounded proxies, which has been applied in genetic epidemiology to circumvent issues of confounding and reverse causation (Skrivankova et al., 2021; Deng et al., 2023). Since the genotype subgroups were randomly inherited from parents to offspring, independent of concerning confounding factors that influenced the exposure of interest (known as SNPs) and unaffected by reverse causation, if instrumental variable assumptions are all met.…”
Section: Introductionmentioning
confidence: 99%
“…As a statistical approach reminiscent of randomized controlled trials, Mendelian randomization (MR) utilizes genetic variation to determine whether the association observed between a risk factor and outcomes is indicative of the existence of a causal relationship [ 15 , 16 ]. Although confounding bias and reverse causality are common limitations in observational studies, they are less likely to appear in MR analyses since genotype formation precedes disease onset [ 17 ]. Several MR analyses have confirmed the causal relationship between IPF and exposures such as body mass index (BMI) [ 18 ], circulating proteins [ 19 ], comorbidities (including gastroesophageal reflux disease (GERD) [ 20 ], hypothyroidism [ 21 ], venous thromboembolism [ 22 ], chronic obstructive pulmonary disease [ 22 ], and diabetes [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%